2018
DOI: 10.3389/fphys.2018.01653
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Responses to Different Cry1Ac Selection Stresses in Helicoverpa armigera

Abstract: Helicoverpa armigera can develop resistance to Bacillus thuringiensis (Bt), which threaten the long-term success of Bt crops. In the present study, RNAseq was employed to investigate the midgut genes response to strains with different levels of resistance (LF5, LF10, LF20, LF30, LF60, and LF120) in H. armigera. Results revealed that a series of differentially expressed unigenes (DEGs) were expressed significantly in resistant strains compared with the LF-susceptible strain. Nine trypsin genes, ALP2, were downr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 72 publications
2
31
0
Order By: Relevance
“…The significantly downregulated of APN1 in the Cry1Ac‐resistant Trichoplusia ni lead to the resistance to Cry1Ac (Tiewsiri & Wang, 2011). And we found that the downregulated of ALP and APN generally existed in the Cry1Ac‐resistant strain (Wei et al, 2018b). Here we found the relative expression level of polycalin significantly reduced both at the protein level and the transcript level in the Cry1Ac‐resistant H. armigera strain.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…The significantly downregulated of APN1 in the Cry1Ac‐resistant Trichoplusia ni lead to the resistance to Cry1Ac (Tiewsiri & Wang, 2011). And we found that the downregulated of ALP and APN generally existed in the Cry1Ac‐resistant strain (Wei et al, 2018b). Here we found the relative expression level of polycalin significantly reduced both at the protein level and the transcript level in the Cry1Ac‐resistant H. armigera strain.…”
Section: Discussionmentioning
confidence: 96%
“…Cadherin fragment from Anopheles gambiae and Manduca sexta could enhance the insecticidal activity of Cry4Ba and Cry1Ab, respectively (Peng, Xu, Ye, Yu, & Sun, 2010). Overexpression ALP and APN in the insect cells could significantly increase the toxicity of Cry1Ac (Wei, Liang et al, 2016; Wei, Yang et al 2018). Stevens, Song, Bruning, Choo, and Baxter (2017) reported they expressed P. xylostella ABCC2 gene in transgenic Drosophila caused this transgenic Drosophila susceptible to Cry1Ac.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Likewise, Cry1Ac resistance was found to be tightly linked to downregulation of ALP in Plutella xylostella . The fact that HaALP1 and HaALP2 were upregulated and downregulated (Wei et al, 2018), respectively, in several Cry1Ac-resistant strains of this pest, suggests that HaALP1 is probably a soluble ALP and functions as a Cry1Ac sequesterer, whereas HaALP2 is an m-ALP and acts as a Cry1Ac receptor. In two Cry1Ac-resistant strains of H. zea, resistance probably resulted from a 10-fold increase of a soluble ALP (~68 kDa) secreted into the midgut lumen, which sequestered many of the ingested Cry1Ac toxins in the midgut lumen, thus not only preventing them from binding to the midgut receptors, but also exposing them for additional proteolysis degradation to occur (Caccia et al, 2012).…”
Section: Introductionmentioning
confidence: 98%